Evolution of mobile group I introns: recognition of intron sequences by an intron-encoded endonuclease. - Loizos, N (1994)
Mobile group I introns are hypothesized to have arisen after invasion by endonuclease-encoding open reading frames (ORFs), which mediate their mobility. Consistent with an endonuclease-ORF invasion event, we report similarity between exon junction sequences (the recognition site for the mobility endonuclease) and intron sequences flanking the endonuclease ORF in the sunY gene of phage T4. Furthermore, we have demonstrated the ability of the intron-encoded endonuclease to recognize and cleave these intron sequences when present in fused form in synthetic constructs. These observations and accompanying splicing data are consistent with models in which the invading endonuclease ORF is provided safe haven within a splicing element. In turn the intron is afforded immunity to the endonuclease product, which imparts mobility to the intron.